TECHNOLOGICAL RISKS IN THE DISMANTLING OF CRANE STEEL STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2024)
The article analyses unfavorable factors arising during dismantling and moving of crane structures, mechanical equipment in the conditions the urban transport network, access roads to the long-term storage warehouse. Paper is based on the analysis the causes accidents and emergencies and shows that many them are man-made (technical condition of buildings, structures, equipment and engineering networks, poor  organization  work  technology).Article  presents  developments  in  the  analysis  process  of dismantling a tower crane in the conditions limited space a construction site, urban development. Purpose of the research - identify factors affecting the safety dismantling process, analyses and systematize data e progress work in a cramped construction site and identify options dismantling cranes that are most beneficial enterprise. Proposed methodology is aimed at reducing the risks of the technological process dismantling crane structures, which is an urgent task in the field construction. Assessing  principles  the  conditions  limited  space  a  construction  site  during  construction depending on the technology work production are presented. Recommendations for dismantling metal structures tower-type cranes and determining technological safety are given. Methodology  allows  identifying  and  assessing  risks  when  planning  the  decommissioning procedure for a tower crane. In this case, it is possible to optimize material costs economically to reduce  the  overall  cost  of  construction.  The  efficiency  of  this  method  is  increased  when decommissioning several cranes involved in construction. Study of the state structures, considering the most unfavorable combination influences, was considered in accordance with the methodological approach to substantiate composition and structure parameters  of  structural  durability  for  managing  technological  safety  by  reducing  risks.  The possibility ensuring service life structures through the combined use of analysis methods has been established, which is due to the rational design, development and use advanced means planning and ensuring the technology of construction processes.